A speed-accurate self-sustaining head direction cell path integration model without recurrent excitation. (2nd October 2018) - Page, Hector J. I.; Walters, Daniel; Stringer, Simon M.
ABSTRACT: The head direction (HD) system signals HD in an allocentric frame of reference. The system is able to update firing based on internally derived information about self-motion, a process known as path integration. Of particular interest is how path integration might maintain concordance between true HD and internally represented HD. Here we present a self-sustaining two-layer model, capable of self-organizing, which produces extremely accurate path integration. The implications of this work for future investigations of HD system path integration are discussed.